CONTRIBUCIÓN A LA GEOLOGÍA Y GEOMORFOLOGÍA DE UNA PARTE DEL CANTÓN DE CORONADO; COSTA RICA - Vargas Sanabria, Asdrúbal (2011)
The geology of the area is defined by basaltic and andesitic lava flows, mud flows, tuffs, alluviumdeposits and ash. The basaltic lavas are correlated with the Aguacate Group and the andesitic lavas with the Irazú volcano. The geomorfological features of the río Virilla microbasin indicate that it has a recent development with morechannels per square kilometer. The río Durazno microbasin is very narrow and the path of the water to the exit islonger. The geomorphology is composed of six units and there are two main units, one of transition (5-21°) or highslope (15°-35°). The regulation plan of management for the Coronado county must consider information upon geol-ogy, geomorphology, and natural hazard. This work is neccesary for the implementation of a geografical informationsystem and to improve the soil use management.